TOURISM STRATEGY OF ALBANIA - Marku, Aida (European Scientific Journal, ESJ, 2014)
Tourism has been identified as a major tool for the development of any country because it is a key role in developing it. First, it is likely that tourism will be amongst the most important or valuable international business. Second, it is also likely that tourism be utilized as a means for attracting international development financial aid. Third, tourism promotional activities will be used as an instrument for improving a country's image. Albania is recognized as a tourism destination at the Mediterranean coast and has a competitive position in the international tourism market. In order to fulfill the mission for achieving the above-mentioned vision, the success of this strategy lies on the partnership of the main actors of tourism sector. The mission of the tourism partners is described as follows: Welcome the guests and therefore understand hospitality and high quality of service as the most important elements within the tourism product Protect and even develop actively the environment Support the culture On the paper below the stress will be on the tourism strategies because they are very important and the responsible institutions will have to do the needed policies.